Midline versus anterolateral incisions for total knee arthroplasty—a systematic review and analysis of the angiosomes of the knee. Issue 10 (17th August 2021) - Slattery, David; Langston, Joseph; Shumack, Matthew; Young, David; Taylor, Ian
Abstract: Introduction: The most common incision for total knee arthroplasty is the anterior midline incision; however, it is commonly associated with lateral knee numbness, kneeling difficulties and restricted flexion range. We sought to review the literature regarding the neurovascular supply and angiosomes over the anterior knee, and evaluate the anterolateral incision as a viable alternative for knee arthroplasty. Methods: A systematic review of the literature was performed searching PUBMED, MEDLINE and EMBASE to evaluate the incisions available for total knee arthroplasty with respect to neurological function, kneeling ability and complications. Results: Ten studies were identified evaluating midline or anterolateral incisions for total knee arthroplasty, with a total of 664 knees for analysis. Mean patient age was 68 years (45–88), and average length of followup was 1 year. A total of 586 had an anterior midline incision and 78 had an anterolateral incision. A total of 62% of anterior midline incisions sustained altered sensation compared to 15% (12/78) of anterolateral incisions ( p < 0.0001). Incision length was similar in both groups (19.8 cm midline vs. 20.8 cm anterolateral). Wound dehiscence was not significantly different between the two groups being 8.3% for midline incisions, and 2.5% for anterolateral incisions ( p = 0.153). Kneeling ability was reported in two studies which reported an improved ability to kneel with an anterolateral incision. Conclusions: The lateral parapatellar incision respects the neurovascular anatomy of the knee and offers a significant reduction in sensory changes, better kneeling ability and similar rates of wound problems to a standard midline incision and should be considered as a viable alternative for knee arthroplasty. Abstract : We review the anterolateral incision for knee arthroplasty, with particular reference to the angiosomes of the knee, and show that it is a safe alternative for total knee arthroplasty.